Applied auditing - Cabrera, Ma. Elenita Balatbat (Manila, Philippines : Conanan Educational Supply, 2011)
Auditing is a systematic process by which a competent, independent person objectively obtains and evaluate evidence regarding assertions about economic actions and events to ascertain the degree of correspondence between those assertions and established criteria and communicating the results to interested users.
Unit I. Overview of the Audit Process; Audit Planning -- Unit II. Evidence Accumulation and Evaluation - Interim Audit Phase: Tests of Controls and Substantive Tests of Transactions -- Unit III. Evidence Accumulation and Evaluation - Final Audit Phase: Substantive Tests of Balances and Analytical Procedures -- Unit IV. Completing the Audit and Report Preparation.
Includes bibliographical references.
Keywords: AUDITING